Pengembangan Potensi Desa Nusa Sebagai Kawasan Destinasi Wisata Terpadu Berbasis Mobile Android - Munawir Munawir; Erdiwansyah Erdiwansyah; Susmanto Susmanto; Zulfan Zulfan (PTE FTK UIN Ar-Raniry, 2023)
Nusa Village's local potential continues to be realized into various tourist attractions with the primary goal of improving the community's economy and maintaining environmental sustainability. Processing goods made from organic waste, culinary tours, homestays, and beautiful scenery with village nuances are some of the potentials in the village of Nusa. Many things can be grown in Nusa village; it is appropriate to promote and serve as an integrated tourist destination. The goal of this research is to use information technology to increase the potential of Nusa Village as an integrated tourist destination area. One application of information technology is the use of Geographic Information System (GIS) and Android mobile devices. Looking at the potential condition of the Nusa Tourism Village, it is a form of community empowerment that prioritizes sustainable development goals in order to increase people's income. Based on the potential of Nusa Village, it should be used as an integrated tourist destination area in Aceh Besar, so it is necessary to have supporting facilities, provide information to tourists, create a form of promotional media, and also a marketplace to sell handicrafts, so that it has a place to sell works. It is hoped that the development of this application will help to increase people's income in the aftermath of COVID-19. This research yields an android-based application, which will be used by the village of Nusa to map the location of tourism potential, and then by the women's group Nusa Creation Community (NCC), which creates handicrafts. They can be sold by the craftsmen through this marketplace system. This application provides tourists with information so that they can easily visit all destinations, and tourists can use it to buy handicrafts in a system.